Evaluation of the Antioxidant and Antibiofilm Activities of Rosmarinus Officinalis Essential Oil Extract - Ahmed H. AL-Azawi; Kais Kassim Ghaima; Noor Saad Latteef; Alaa Aziz Abdulhassan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Biological activities of essential oils from various plants, including Rosemary, have been attributed to thepresence of specific chemical compounds with antimicrobial, anti-inflammatory and antioxidant activities.The aim of this study is to estimate the antioxidant and antifungal activity of Rosmarinus officinalis essentialoil extract. The study included the extraction of essential oil using a Clevenger apparatus. The chemicalcompositions were evaluated by GC-MS and High Performance Liquid Chromatography (HPLC).Therosemary essential oil extract was tested with regard to antioxidant utilizing 2, 2- diphenyl-1-picrylhydrazyl(DPPH) assay. Microtiter plate Assay used to determine the antifungal and antibiofilm activity. The resultshowed that the GC-MS analysis revealed that the major components determined in R. officinalis essentialoil were linalool (17.09 %), L- Borneol (11.92 %), Verbenone (8.52 %), camphor (5.30 %), Eucalyptol(4.79 %), while the chemical compositions identified by HPLC shows four phenolic acids were identifiedin the essential oil, Rosmarinic acid, Caffeic acid, p-Coumaric acid, 4-hydroxybenzoic acid, and lignans(medioresinol), while Isorhamnetin was the only flavonol detected. The free radicals scavenging activityincreased gradually with the increase in the concentration of essential oil which was 81.59 % whencompared with BHT and V.C (92.34 and 97.42) respectively. The results of the antifungal activity revealedthat Minimum Inhibitory Concentration of C. albicans and C. krusei was 3.125%, while the MIC of C.glabrata was 12.5% in contrast with the highest MIC which recorded for C. tropicalis at 25% of rosemaryessential oil. The current results revealed that the reduction of bofilm formation among C. albicans andC. krusei was obvious at the lower concentration (1.56%), where the percentage of biofilm formation inC. albicans was (91.25%) and C. krusei was (84.25%), while C. tropicalis exhibit (86.32%) for biofilmreduction at the concentration (12.5%) of rosemary essential oil, also it was found that the effect of essentialoil on C. glabrata biofilm formation was at the concentrations 3.125% and 6.25%. The findings of this studyindicated to the significant effect of rosemary essential oil against the growth and biofilm formation of theimportant pathogenic yeast C. albicans at low concentrations.